A Study of the Patterns and Characteristics of Successful Community Forest Management Participation: A Case Study in Kalong Subdistrict, Si Sakhon District, Narathiwat Province. - ตูแวปูเต๊ะ, กูพะดี; เจ๊ะนุ, บิสมี; บัวแก้ว, โนรซาฮาดา; ผูหาดา, ฮากีม (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research, entitled “A Study of the Patterns and Characteristics of Public Participation in Successful Community Forest Management: A Case Study of Kalong Subdistrict, Si Sakhon District, Narathiwat Province,” aims to (1) examine the patterns and characteristics of public participation in community forest management, and (2) explore approaches to promoting public participation in community forest management. This study employed a qualitative research approach. Key informants were selected using purposive sampling and included community leaders, community forest committee members, religious leaders, and local residents. Data were collected through in-depth interviews and field observations and analyzed using content analysis.        The findings revealed that public participation in community forest management consists of four main aspects: participation in decision-making, implementation, benefit sharing, and monitoring and evaluation. The community plays a significant role in establishing rules, conserving forest resources, and utilizing resources appropriately in accordance with the local context. In terms of promoting public participation, the study suggests encouraging continuous involvement of community members in all stages of community forest management, supporting community-based activities, and enhancing awareness of forest conservation. These approaches contribute to strengthening community forest management and ensuring its long-term sustainability.